Criminogenic Influence of Mass Media on Consciousness of Local or Mass Audiences and Varieties of its Negative Consequences - Pakhnin, Mykola (Archives of Criminology and Forensic Sciences, 2022)
Criminogenic influence of mass media on consciousness of local or mass audiences and varieties of its negative consequences. On the analysis basis of various doctrinal criminological positions, normative provisions of current legislation of Ukraine and existing judicial practice, the concept of criminogenic influence of mass media on consciousness of an individually defined person or group of people is determined, various types of its negative consequences are singled out, and on this basis, own generalized conclusions are determined. This article purpose is to define the criminogenic influence concept of mass media on consciousness of local or mass audiences, identify its signs, various types of negative consequences, and to formulate one’s own generalized conclusions on this basis. Criminogenic influence of the mass media is a negative informational and psychological influence on consciousness of a person or a group of people consisting in interaction of the mass media with a local or mass audience, i.e. in dissemination of destructive information about the of influence object by mass media, that leads to distortion of consciousness of a person or group people regarding the perception of surrounding objective reality and forms their determination to commit various types of deviant practices as a justified and rightly chosen behavior choice, which result is the onset of negative legal consequences. These consequences can be represented by legal responsibility for illegal, socially dangerous activity of legal entities and individuals in the form of criminal, administrative or civil liability, measures of a criminal legal nature against legal entities or other restrictive measures, which content are certain restrictions on property, physical, organizational, legal or other nature.